Plasma Carbonization of Sustainable Lignin Fiber‐Derived Papers for Supercapacitor Electrodes - Philipp A. Schuster; Chinmaya Mirle; Lisa Kuske; Frank Schmidt; Michael R. Buchmeiser; Felix Rohrbach; Joachim Bansmann; Stefan Terbrack; Holger Heuermann; Erik Frank; Alexander J. C. Kuehne (Macromolecular Materials and Engineering, 2025)
Abstract The majority of carbon materials on the market are produced from polyacrylonitrile precursor fibers using high‐temperature oven processes. Despite approaches for green carbon fiber precursors, current stabilization and carbonization processes require large amounts of energy and render carbon materials costly and environmentally not sustainable. Here, a plasma carbonization treatment is employed for papers made from lignin/polyvinylpyrrolidone precursor fibers. The process provides carbonization within a timeframe of a few seconds, while the degrees of porosity, conductivity, and hydrophobicity can be tuned. It is shown that the properties of these carbonized papers are suitable for application as supercapacitor electrodes with capacitances in the range of 40 mF g−1 with very good cycling stability dropping by less than 20% over 4000 cycles.